Efficacy of Subcutaneous Morphine Patient Controlled Analgesia Compared to Intravenous Morphine Patient Controlled Analgesia on Cesarean Section - Wiryana, Made; Sinardja, I Ketut; Budiarta, I Gede; Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gde; Aribawa, I Gusti Ngurah Mahaalit; Nainggolan, Elisma (Bali Journal of Anesthesiology, 2017)
Background: Cesarean section causes moderate to severe pain in the first 48 hours postoperatively, thus requiring an adequate perioperative pain management, not only so that the mother can be quickly discharged but also to perform daily activities after surgery such as breastfeeding and nurse the baby.Objective: To determine the efficacy of subcutaneous morphine patient controlled analgesia (SC-PCA) in lowering VAS (visual analogue score), total morphine consumption and postoperative side effect on cesarean section compared with intravenous morphine patient controlled analgesia (IV- PCA).Methods: This study is an experimental clinical trial using consecutive sampling technique. Sixty-four subjects were allocated into two groups of PCA morphine subcutaneously (SC-PCA) and the group PCA morphine intravenously (IV-PCA), each consisting of 32 subjects using permuted block randomization. Morphine concentration was 5 mg/ml (group SC-PCA) or the concentration of 1mg/ml (group IV-PCA). Both groups were then analyzed for VAS ratings, total morphine consumption, and adverse effects, post operatively at 4th, 8th, and 24th hour. Statistic analysis using repeated ANOVA test and t-test with p <0.05 onsidered significant.Result: Morphine consumption in IV-PCA group showed lower needs than SC-PCA (9.41 mg vs 4,9mg) p <0.001 24 at 24 hours postoperatively. The VAS at resting at 4th hours statistically significantly lower in IV-PCA group (1.06 ± 0.71 vs 0.81 ± 1.40, p=0.029) and at 8th hours (1.03 ± 0.59 vs 0.94 ± 0,9, p=0.048). The moving VAS at 4th hours statistically significant lower in IV-PCA group (2.31 ± 0.47 vs 1.45 ± 2.06, p=0.019) but the static or VAS at moving are not different clinically. Side effects of nausea and vomiting are more common in IV-PCA group. We conclude that SC-PCA provide analgesia more effective and decreases side effects in patients undergo sectio cesarea with spinal anesthesia.